Some reflections on Christian and Islamic political thought - Goddard, Hugh (Islam and Christian-Muslim relations, 1990)
There is a widespread view that one of the essential differences between Islam and Christianity is their attitudes towards politics and the state: Christianity, it is argued, is not essentially concerned with these things but rather with spiritual matters, while for Islam politics and the state are an integral element of it. This paper argues that such a view neither accords with the historical evidence for the development of the two traditions nor takes account of the diversity that exists within them on this question: and it concludes that a more judicious description is that Christianity is concerned with politics, if not the state, while Islam is concerned with both and considers the state to be itself a religious institution.